SLEEP MODE FOR USER EQUIPMENT RELAYS - BHUSHAN, Naga; WEI, Yongbin; DAMNJANOVIC, Aleksandar; MALLADI, Durga Prasad (2019)
Certain aspects of the present disclosure provide methods and apparatus for subframe muting and/or discontinuous reception (DRX) mode related to sleep mode for user equipment (UE) relays. One method generally includes measuring, at a UE functioning as a relay (i.e., a UE relay), signals of one or more other UEs functioning as relays during one or more particular subframes and reporting the measurements of the signals to an apparatus. Another method generally includes determining, at a first UE functioning as a relay, that no UEs are being served by the first UE; based on the determination, increasing an interval between broadcast signals; and transmitting the broadcast signals according to the increased interval.